A Framework Studies of Sustainable Eco Urbanspace - Nurakmal, Abdullah@ Goh Tuo Ho; Roshanfekr, S.; Che Ani, A. I.; Norngainy, Mohd Tawil; Noraini, Hamzah (Maxwell Scientific Organization, 2013)
In this study the researcher introducing eco urban sustainable and explain about its components. It also mentions the relationship between urban and green with the description about the elements of sustainable green criteria in eco urban. Urban is known as a place with higher population density, very large proportion of the population live in urban area. They need great facilities for a comfortable life. Being complete of this feature shows the progress of urban development. The urban is a place for living activities, business opportunities, shopping centers, transportation and housing and lots of acting which is related with living. These activities makes urban polluted, noisy, crowded and populous. A city reaches to the sustainability once the planning managers and officials solved urban issues and problems. This strengthens its capabilities with policy, creativity and knowledge considering the abilities and potential which cities have.